Internalizing sustainable practices: a configurational approach on sustainable forest management of the Dutch wood trade and timber industry. (16th November 2015) - Chappin, Maryse M.H.; Cambré, Bart; Vermeulen, Patrick A.M.; Lozano, Rodrigo
Abstract: A number of environmental labels and certificates have been developed to inform consumers of the environmental impacts. This paper explored different configurations of institutional and organizational conditions for the internalization of sustainable practices. For the institutional conditions the level of institutional pressures were considered. For the organizational conditions the following elements were taken into account: 1) the timing of adoption; 2) the willingness to cannibalize existing capabilities and routines to incorporate institutional demands for sustainability; 3) the degree of implementation of these demands; 4) the internal representation of environmental concerns; and 5) the type of organization. The paper analyzed sustainable forestry practices in wood trade and timber factories in the Netherlands using a fuzzy set Qualitative Comparative Analysis. From the analysis, three configurations were found: 1) concerned internalization, for early adopting wood trade companies; 2) forced internalization, for late adopting wood trade companies; and 3) lagged internalization, for late adopting timber factories. The configurations revealed that important conditions for explaining internalization of sustainable practices are high levels of implementation and high levels of willingness to cannibalize. The findings reaffirm the relevance of institutional and organizational conditions in explaining the internalization of environmental friendly practices. They also showed that the interplay between a firm's internal and external environments influence the internalization of environmental practices. The results imply that practice internalization is more subtle than previously understood in the literature. Highlights: The study revealed three configurations for internalization of sustainable practices. The interplay of institutional and organizational conditions is important. Active implementation is important for internalization of sustainable practices. Willingness to cannibalize is important for internalization of sustainable practices.